Srī gurumata sākhī pramāṇa : Srīgurūgrantha Sāhiba jī dīāṃ tukāṃ para pañja sau paintī sākhīāṃ - Jodha Siṅgha, 1882-1981 (SAMP early 20th-century Indian books project ;)
Anecdotes from Ādi-Granth, Sikh canon.